Computed Tomography Cinematic Rendering in the Evaluation of Colonic Pathology: Technique and Clinical Applications. Issue 3 (May 2019) - Rowe, Steven P.; Chu, Linda C.; Fishman, Elliot K.
Abstract : Abstract: Three-dimensional (3D) visualizations of computed tomography (CT) data have found use in the display of complex anatomy and pathology. A new method of 3D CT image creation known as cinematic rendering (CR) makes use of a global lighting model to produce photorealistic images. Cinematic rendering images contain high levels of detail with shadowing and depth that are not available from traditional 3D CT techniques. As yet, the role of CR in evaluating colonic pathology has not been investigated. However, given the breadth of pathologic processes that affect the colon, including inflammatory bowel disease, diverticulitis, neoplastic conditions, herniation, and gastrointestinal bleeding, we undertook a survey of recent cases at our institution to demonstrate colon pathology as visualized with CR. The following review discusses the role of 3D CT visualizations for colonic pathology with an emphasis on CR example images.